Classical and Statistical Optimization of Medium Composition for Promoting Prodigiosin Produced by Local Isolate of Serratia Marcescens - Mohammed, Sura Jasem; Kadhum, Khalid Jaber; Hameed, Khalid waleed (Al-Khwarizmi Engineering Journal, 2018)
Prodigiosin is a ‘natural red pigment produced by Serratia marcescens which exhibits immunosuppressive and anticancer properties in addition to antimicrobial activities. This work presents an attempt to maximize the production of prodigiosin by two different strategies: one factor at time (OFAT) and statistical optimization. The result of OFAT revealed that sucrose and peptone were the best carbon and nitrogen sources for pigment production with concentration of prodigiosin of about 135 mg/ L. This value was increased to 331.6mg/ L with an optimized ratio of C/N (60:40) and reached 356.8 with pH 6 and 2% inoculum size at end of classical optimization. Statistical experimental design based on Response surface methodology was conducted to optimize the composition of trace element. The design revealed that the predicted prodigiosin production of 406 mg/L can be achieved when concentrations of trace element CaCl2·2H2O, FeSO4·4H2O, MgSO4·7H2O and MnSO4·4H2O were equal to 9.22, 0.32, 0.67 and 2.48 g/L, respectively. The actual production of prodigiosin in the optimized medium was 375 mg/L. Growth kinetics of S. marcescens were evaluated in optimized medium which revealed that prodigiosin was ‘non-associated growth’ secondary metabolite with maximum production of approximately 365.7 mg/L obtained after 54 hours of incubation.